Energy Management system for Hybrid RES with Hybrid Cascaded Multilevel inverter - Naveen Kumar; J. Baskaran (Institute of Advanced Engineering and Science, 2014)
In this paper, we propose an energy management system with hybrid solar and wind renewable energy system (RES) with Multilevel inverter to give a lossless power to load. This system continuously receives the battery storage and power consumption after it checks the these value with default value if power consumption is exceeds default value means it turn off the loads. We are assigns the priority to the loads in order to overcome the user inconvenient. To increase PV module output MPPT is used. The existing system uses only boost converter, in our paper boost converter is combined with buck converter used because the PV module can produce high voltage than DC-bus voltage. Buck converter used to step down purpose. In this system on-line configuration check and buck-boost mode transition will be presented. Experimental results measured from three-string MPPTs with EMS the maximum power level of 10 kW are used to verify the analysis and discussion with hybrid cascaded multilevel inverter.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4529